Evaluation of taro [ Colocasia Esculenta (L.) Schott] flour as a hydrocolloid on the physicochemical, rheological, and sensorial properties of milk pudding - Hendek Ertop, Müge; Atasoy, Rabia; Akın, Şeyma Selin (Wiley, 2019)
The taro (Colocasia esculenta) flour was evaluated to the preparation of the milk pudding as a hydrocolloid. The physicochemical properties of taro flour were compared with corn starch and rice flour which generally take place in pudding mix, then they were incorporated into pudding formulation at the different ratios. The taro flour was found significantly (p < 0.05) different from rice flour and corn starch, due to its higher ash, fiber, fat and protein content, and color properties. Taro starch granules exhibited irregular, polygonal shapes, and small particle size visually in scanning electron micrographs. The increased concentration of taro flour in the pudding samples resulted in obtaining higher ash, protein, fiber, fat and mineral contents, and viscosity. All pudding samples exhibited pseudoplastic behavior. The samples which contained more taro flour scored the highest in terms of thickness and viscosity; however, “smoothness/grittiness acceptance” scored lowest due to the properties of mouth feeling. Although the taro flour had 45.42% bioavailability rate due to owned antinutrients, the pudding samples had higher rates because of the cooking process. PRACTICAL APPLICATIONS: The most important features expected from a texturizing agent such as taro flour are that it has a neutral taste/aroma and is compatible with other components. The study revealed that taro flour could be valorized as fortifying and hydrocolloid ingredient in pudding type products. Due to its high water binding capacity, it can be used with together other hydrocolloid thickening ingredients such as starch and gums. It can also be evaluated as a fortifying agent due to high mineral and fiber contents. To obtain smooth taro flour particles in the mouth, the alternative milling techniques can be applied to produce taro flour which has more small flour particles. Because the taro is rich in nutritive content and is comparatively cheaper than other roots and tubers, promoting and evaluating such taro‐processed products is important industrially.
Keywords: 2. Zero hunger